2020
DOI: 10.1002/agj2.20483
|View full text |Cite
|
Sign up to set email alerts
|

Effect of magnesium fertilizer combined with straw return on nitrogen use efficiency

Abstract: Improving nitrogen use efficiency (NUE) has great significance for agriculture sustainable development and reducing environmental pollution. The effects of Mg fertilizer combined with straw return on yield, N uptake, and NUE of spring maize (Zea mays L.) were investigated for two consecutive years. The treatments included JM3 (straw + magnesium fertilizer), JM0 (straw + no magnesium fertilizer), WM3 (no straw + magnesium fertilizer), and WM0 (no magnesium fertilizer + no straw). The application of Mg fertilize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…The appropriate combination and effective doses of essential elements can positively improve the yield and quality of turmeric [18]. Soils deficient in active nutrients may negatively impact the quality and effectiveness of medicinal plants [19]. Improving plant nutrition will improve the quantity and quality of turmeric [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The appropriate combination and effective doses of essential elements can positively improve the yield and quality of turmeric [18]. Soils deficient in active nutrients may negatively impact the quality and effectiveness of medicinal plants [19]. Improving plant nutrition will improve the quantity and quality of turmeric [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…41 There were also studies that showed straw returning or straw returning combined with biochar effectively decreased N and P concentrations in surface water. 40,42 Straw returning reduced the loss of N and P mainly by reducing runoff and sediment.…”
Section: Resultsmentioning
confidence: 99%
“…> 70% N > 70%N50%P+Straw > CK. Straw returning was an effective, eco-friendly tillage method for decreasing reactive N loss via surface runoff . The average loss of TP was 0.04–0.60 kg·ha –1 with the order of average loss of TP: Conv.…”
Section: Resultsmentioning
confidence: 99%
“…Various studies have shown that higher Mg concentration enhances the plant resistance to various environmental stresses such as light, heat, and drought (Cakmak, 2013;Gransee and Führs, 2013;Mengutay et al, 2013). Moreover, Mg deficiency also interferes with N metabolism, which has important implications for crop production and the environment (Grzebisz, 2013;Zhang et al, 2021). Therefore, Mg deficiency would affect plant development and the formation of yield and quality.…”
Section: Strengthening Mg and Optimizing Npk To Further Increase Yieldmentioning
confidence: 99%